The Role of Knowledge and Penetration of Fintech Services in Improving MSMEs of Fishermen and Marine Farmers in Remote Small Islands Region - Frischilla Pentury (Universitas Airlangga, 2023)
Objective: This study aims to investigate the impact of knowledge and current penetration of fintech services on the overall performance of micro, small, and medium-sized enterprises (MSMEs), which in this case were fishermen and marine farmers. Design/Methods/Approach: This study utilized data from nine fishing villages with two hundred respondents. The data was collected using a questionnaire based on the purposive sampling technique, then analyzed using SmartPLS and path analysis. Findings: Knowledge had direct and indirect positive and significant effects on the overall managerial performance of fishermen and marine farmers. In addition, the user experience might increase the rapid adoption of fintech, improving the performance of MSMEs in small island regions. Originality/Value: This study highlights the importance of fintech knowledge for increasing the uptake and impact of fintech among MSMEs in remote small island areas, which has escaped the attention of scientific research. Practical/Policy implication: Given the results, more effort is needed to increase the knowledge of MSMEs in small islands region regarding services and risk to increase the participation of MSMEs in fintech.